Postdramatic tragedies - Cole, Emma ca. 20./21. Jh (Oxford University Press, 2019)
Ancient tragedy has played a well-documented role in contemporary theatre since the mid-twentieth century. In addition to the often-commented-upon watershed productions, however, is a significant but overlooked history involving classical tragedy in experimental and avant-garde theatre. This text focuses upon such experimental reinventions and analyses receptions of Greek and Roman tragedy that come under the banner of 'postdramatic theatre', a style of performance in which the traditional components of drama, such as character and narrative, are subordinate to the immediate, affective power of more abstract elements, such as image and sound
This edition also issued in print: 2020. - Includes bibliographical references and index
Keywords: Geschichte 1995-2015; Tragedy / History and criticism; Greek drama (Tragedy) / Influence; Greek drama (Tragedy) / Adaptations / History and criticism; Griechisch; Tragödie; Experimentelles Theater; Englisch; Latein; Rezeption